2020
DOI: 10.3390/genes11040465
|View full text |Cite
|
Sign up to set email alerts
|

A New SNP in Rice Gene Encoding Pyruvate Phosphate Dikinase (PPDK) Associated with Floury Endosperm

Abstract: Rice varieties with suitable flour-making qualities are required to promote the rice processed-food industry and to boost rice consumption. A rice mutation, Namil(SA)-flo1, produces grains with floury endosperm. Overall, grains with low grain hardness, low starch damage, and fine particle size are more suitable for use in flour processing grains with waxy, dull endosperm with normal grain hardness and a high amylose content. In this study, fine mapping found a C to T single nucleotide polymorphism (SNP) in exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Interestingly, we found three isoforms of PPDK, all of them upregulated from 12 to 26 DAA (Table S11 ). Several proteomic studies reported that multiple isoforms of PPDK accumulate at high levels in the developing grain of cereals such as rice (Xu et al., 2008b ) and wheat (Ma et al., 2014b ), indicating that PPDK has an essential role in starch synthesis and energy supply during grain development (Wang et al., 2020 ). PPDK catalyzes the reversible conversion of pyruvate, ATP, and Pi to phosphoenolpyruvate (PEP), AMP, and PPi (Yu et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found three isoforms of PPDK, all of them upregulated from 12 to 26 DAA (Table S11 ). Several proteomic studies reported that multiple isoforms of PPDK accumulate at high levels in the developing grain of cereals such as rice (Xu et al., 2008b ) and wheat (Ma et al., 2014b ), indicating that PPDK has an essential role in starch synthesis and energy supply during grain development (Wang et al., 2020 ). PPDK catalyzes the reversible conversion of pyruvate, ATP, and Pi to phosphoenolpyruvate (PEP), AMP, and PPi (Yu et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Starch is the major carbohydrate in rice grains, of which approximately 18% is amylose and 82% is amylopectin [4]. The ratio of amylose to amylopectin plays an important role in the rice grain structure, appearance, and eating quality.…”
Section: Introductionmentioning
confidence: 99%
“…The gene ZmPPDK1 encodes an essential photosynthetic enzyme in maize, a C4 plant. By contrast, the rice ortholog OsPPDK1 (LOC_Os05g33570, Os05g0405000) has no role in photosynthesis but rather plays an important role in starch biosynthesis and during seed development ( Kang et al., 2005 ; Zhang et al., 2018 ; Wang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%